Hybrid Congestion Control Mechanism in Software Defined Networks - Sood , Reecha; Kang , Sandeep Singh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Software-Defined Networking (SDN) has emerged as a promising paradigm to manage network traffic efficiently and provide enhanced performance. Queue management plays a critical role in SDN by effectively controlling the flow of packets and ensuring Quality of Service (QoS). We have implemented WFQ, which provides fairness and QoS guarantees. Assign weights to different flows based on their importance or priority, ensuring equitable distribution of network resources. WFQ dynamically adjusts transmission rates based on flow weights, preventing congestion, and maintaining optimal performance.Monitor queue lengths and implement policies to trigger congestion control measures when thresholds are exceeded. These measures may include queue length, goodput, or notifying source nodes to reduce their transmission rates. This strategy ensures efficient resource allocation, congestion control, and adherence to QoS requirements, resulting in a more robust and responsive SDN environment.